2019
DOI: 10.1177/0022243719831258
|View full text |Cite
|
Sign up to set email alerts
|

Strategic Manipulation of University Rankings, the Prestige Effect, and Student University Choice

Abstract: A multiperiod, theoretical model characterizes the relationship between a publication that ranks universities and prospective students who might use this ranking to decide which university to attend. The published ranking offers information about the universities’ objective quality but also affects their prestige, which may increase student utility. This prestige effect gives the commercial publication incentive to act contrary to the best interest of the students. If a ranking created with the commonly used a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 42 publications
(46 reference statements)
1
24
0
1
Order By: Relevance
“…Therefore, they serve institutional prestige considered very significant for higher education institutions. This inclination follows an understanding that high prestige may increase universities' attractiveness to potential students (Dearden et al, 2019) and is one of the key drivers of students' university choice and attendance (Casidy and Wymer, 2018;Draelants, 2012). Studies also show that universities' reputations significantly affect employers' choice of their future employees (Torche, 2011;Triventi, 2013), and, therefore, seem to impact the future economic benefits of university graduates (Jung and Lee, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…Therefore, they serve institutional prestige considered very significant for higher education institutions. This inclination follows an understanding that high prestige may increase universities' attractiveness to potential students (Dearden et al, 2019) and is one of the key drivers of students' university choice and attendance (Casidy and Wymer, 2018;Draelants, 2012). Studies also show that universities' reputations significantly affect employers' choice of their future employees (Torche, 2011;Triventi, 2013), and, therefore, seem to impact the future economic benefits of university graduates (Jung and Lee, 2016).…”
Section: Introductionmentioning
confidence: 94%
“…More recent contributions have further extended the understanding of the perverse effects of traditional rankings and their metrics [23,31,32]. For example, Dearden, Grewal, and Lilien [31] highlighted that ranking publications, in addition to offering objective information, also affect the prestige of these schools, which in many cases acts against the preferences of students. They concluded that the research capabilities of business schools, which form a heavy component of ranking metrics, introduce the risk of problematic research practices.…”
Section: The Unintended Consequences Of Published Rankingsmentioning
confidence: 99%
“…More recent contributions have further extended understanding of the perverse effects of traditional rankings and their metrics [22,30,31]. For example, Dearden, Grewal and Lilien [30] highlighted that ranking publications, in addition to offering objective information, also affect the prestige of these schools which in many cases acts against the preferences of students. They concluded that research capability of business schools, which forms a heavy component of ranking metrics, introduces the risk of problematic research practices.…”
Section: Perverse Effectsmentioning
confidence: 99%